Spring Forward or Fall Back? : The Post-Crisis Recovery of Firms - Medina, Leandro (IMF Working Papers; Working Paper ;, 2012)
This paper studies corporate performance in the aftermath of the global crisis by examining 6,581 manufacturing firms in 48 developed and developing countries in 2010, identifying factors of resilience as well as vulnerability. Based on a cross-sectional analysis, the results show that pre-crisis leverage and short-term debt have had negative effects on the speed of the recovery, while asset tangibility has had positive effects. The negative effect of leverage is non-linear, being particularly strong in firms with high pre-crisis leverage. Furthermore, the effects are different for advanced and emerging market economies. The paper also shows that the macroeconomic framework critically matters for firm growth. In particular, in countries that have allowed the exchange rate to depreciate, firms have had a faster recovery in sectors highly dependent on trade.